Study on Financing the Destruction of Unwanted Ozone-Depleting Substances through the Voluntary Carbon Market - ICF International (World Bank, Washington, DC, 2017)
This report was prepared by Investment Climate Facility (ICF) international with direction from World Bank's Montreal protocol unit and the project team. While Montreal protocol has achieved remarkable success in reducing production and consumption of ozone depleting substances (ODS) worldwide, a significant amount of ODS still remains in equipments, products, and stockpiles. This report finds that significant opportunity exists for destroying ODS through the voluntary carbon market. The high global warming potential (GWP) of ODS means that their destruction has the ability to generate significant volumes of carbon credits, which could then be sold in the voluntary carbon market. Using the voluntary market is likely a win-win opportunity; incentives are created for the recovery and destruction of ODS through the carbon credits that can be earned, and the buyers pay for real and verifiable emission reductions from the destruction of ODS that would have otherwise been emitted.